2016
DOI: 10.1016/j.pec.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A motivational interviewing-based counseling intervention to increase postabortion uptake of contraception: A pilot randomized controlled trial

Abstract: Objective To determine if a counseling intervention using the principles of motivational interviewing (MI) would impact uptake of long-acting reversible contraception (LARC) after abortion. Methods We conducted a pilot randomized controlled trial comparing an MI-based contraception counseling intervention to only non-standardized counseling. Sixty women 15-29 years-old were randomized. Primary outcome: uptake of LARC within four weeks of abortion. Secondary outcomes: uptake of any effective contraceptive, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 27 publications
(33 reference statements)
0
61
0
Order By: Relevance
“…Women in the intervention group also reported higher rates of satisfaction with counseling than those in the control group (92% versus 65%) (A). 24 Studies have shown that the continuity and satisfaction rates with the contraceptive method are greater when the decision is made by the patient. Women prefer to decide on their contraceptive method autonomously, with less influence of the health professional, and after appropriate advice (B).…”
Section: Counseling and Barriers To Access To Long-acting Methodsmentioning
confidence: 99%
“…Women in the intervention group also reported higher rates of satisfaction with counseling than those in the control group (92% versus 65%) (A). 24 Studies have shown that the continuity and satisfaction rates with the contraceptive method are greater when the decision is made by the patient. Women prefer to decide on their contraceptive method autonomously, with less influence of the health professional, and after appropriate advice (B).…”
Section: Counseling and Barriers To Access To Long-acting Methodsmentioning
confidence: 99%
“…The content of contraceptive counselling heavily influences method selection, especially among younger women. [33][34][35] While it is important to avoid coercion and ensure patient-centred, shared decision-making, we contend that it is time for a more directive approach, one in which women are explicitly informed that LARCs constitute first-line contraception. In this approach, counselling is standardised and methods are presented in order from most to least effective.…”
Section: Fy 2015 Fy 2016 Fy 2017mentioning
confidence: 99%
“…Both motivational interviewing (MI) and person-centred counselling seem to improve the conversation about contraception at the time of an abortion, measured in increased contraceptive uptake [72,73]. Previous research has reported mixed findings regarding contraceptive counselling in the context of an abortion and the effect on contraceptive use post-abortion.…”
Section: Contraceptive Counselling At the Time Of An Abortionmentioning
confidence: 99%
“…Previous research has reported mixed findings regarding contraceptive counselling in the context of an abortion and the effect on contraceptive use post-abortion. Few studies have explored the impact of person-centred counselling or MI at the time of an abortion in clinical practice [17,18,72,73].…”
Section: Contraceptive Counselling At the Time Of An Abortionmentioning
confidence: 99%